2007
DOI: 10.1001/archderm.143.9.1125
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, Biochemical, and Genetic Study of 11 Patients With Erythropoietic Protoporphyria Including One With Homozygous Disease

Abstract: To study the mutations in the ferrochelatase gene (FECH) and the phenotypic expression of erythropoietic protoporphyria (EPP) in a group of Spanish patients. Design: Case series. Setting: University-based hospital. Patients: Eleven unrelated patients with EPP and 19 asymptomatic relatives from 10 families. Main Outcomes Measures: Measurement of protoporphyrin concentration in red blood cells and feces by fluorometry and chromatography. Analysis of the mutations of the FECH gene by single-strand conformation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 30 publications
(44 reference statements)
2
24
0
1
Order By: Relevance
“…These findings are in agreement with the conclusion that the inheritance of a lowexpressed allele together with the mutation in the FECH gene are necessary for the clinical expression of this porphyria (4,13,14,16,(25)(26)(27).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These findings are in agreement with the conclusion that the inheritance of a lowexpressed allele together with the mutation in the FECH gene are necessary for the clinical expression of this porphyria (4,13,14,16,(25)(26)(27).…”
Section: Discussionsupporting
confidence: 90%
“…Although the inheritance of an IVS3-48C allele trans to the mutation explained the phenotypic expression in most families (4,(12)(13)(14), autosomal recessive inheritance can cause overt EPP in patients who do not have the low- expression allele. A small number of cases of recessive inheritance have been reported (15,16). To date, EPP has been diagnosed in 41 individuals from 35 families in our Research Centre on Porphyrins and Porphyrias in Argentina.…”
Section: Introductionmentioning
confidence: 99%
“…The most severe clinical feature is hepatobiliary disease due to protoporphyrin- induced damage to liver cells [298]. Deficiency of the Fe-S enzyme ferrochelatase (FECH), which catalyzes the insertion of ferrous iron into protoporphyrin to form heme, is the most common cause of EPP [299301]. A variant form of EPP has been linked to aberrant splicing of MFRN1 mRNA, which encodes the erythroblastic specific solute carrier mitoferrin 1 (MFRN1, SLC25A37), the major importer of iron into mitochondria in erythroblastic cells [302].…”
Section: Variant Erythropoietic Protoporphyria Caused By Abnormal Expmentioning
confidence: 99%
“…15 In Spain, Herrero reported that three novel mutations (IVS4+1delG, 347-351delC, and 130_147dupl 18) and IVS3-48C low-expression allele in ten of 11 EPP patients. 26 They also estimated the frequency of the IVS3-48C allele among 180 nonporphyric Spanish individuals as 5.2%. 26 In South Africa, Parker identified ten sequence variations; IVS3-48T ⁄ C polymorphism, five further polymorphisms, a 5-bp deletion in exon 7 (757_761delAGAAG), two previously described splice-site mutations (IVS3+2T>G and IVS7+1G>A), and a novel 7-bp deletion in exon 4 (356_362delTTCAAGA).…”
Section: Genetic Characteristics Of Eppmentioning
confidence: 99%
“…26 They also estimated the frequency of the IVS3-48C allele among 180 nonporphyric Spanish individuals as 5.2%. 26 In South Africa, Parker identified ten sequence variations; IVS3-48T ⁄ C polymorphism, five further polymorphisms, a 5-bp deletion in exon 7 (757_761delAGAAG), two previously described splice-site mutations (IVS3+2T>G and IVS7+1G>A), and a novel 7-bp deletion in exon 4 (356_362delTTCAAGA). 27 In Portugal, Morais identified heterozygosity for a novel mutation (c.1052delA) in FECH gene of two children, and heterozygosity for the hypomorphic allele IVS3-48T>C in two children and asymptomatic mother.…”
Section: Genetic Characteristics Of Eppmentioning
confidence: 99%